The characteristic of poverty-alleviation behavioral strategies of the rural poor population and their relationship with socio-demographic factors - Yan Li; Jin-wei Zhu; Yong-quan Huo (Frontiers in Psychology)
ObjectiveThe primary objective of this study is to investigate the fundamental patterns and characteristics of poverty-alleviation behavior strategies among rural poor population. It aims to examine the association between the key socio-demographic characteristics of these populations and their poverty-alleviation strategies, thereby identifying the individual and sociocultural factors related to these behaviors.MethodsThis study employs a questionnaire designed to assess poverty-alleviation behavior strategies among rural poor population. Field surveys were conducted in over 80 natural villages across eight provinces and regions in central, northwestern, and southwestern China, involving 1,457 rural poor population. The data collected were analyzed using a questionnaire assessment method to explore the relationship between poverty-alleviation behavior strategies and socio-demographic factors.ResultsFactor analysis indicates that the poverty-alleviation behavior strategies of rural poor population primarily manifest as fatalism, pragmatism, skepticism, and helplessness. Reliability and validity analyses demonstrate that the Poverty-alleviation Behavior Strategies Questionnaire exhibits high internal consistency reliability, composite reliability, convergent validity, and discriminant validity. Hierarchical regression analysis reveals that socio-demographic characteristics such as health status, educational level, family size, main occupation, and income sources have predictive power regarding the formation of pragmatic and fatalistic poverty-alleviation strategies.ConclusionAmong the four types of poverty-alleviation behavior strategies identified among rural poor population, fatalistic and pragmatic strategies are critically significant for poverty-alleviation efforts and should receive heightened attention from poverty-alleviation workers. While socio-demographic characteristics have limited explanatory power for poverty-alleviation strategies, the sociocultural foundations of pragmatic and fatalistic strategies are relatively more pronounced. Improving the socio-demographic characteristics of rural poor population can, to some extent, facilitate the adoption of pragmatic poverty-alleviation strategies and mitigate the reliance on fatalistic strategies. This conclusion has practical implications for conducting poverty-alleviation work in rural areas.